Pelatihan Pengolahan Bakso Daging Ayam dengan Bahan Pengisi Tepung Labu Kuning bagi Kelompok Wanita Kelurahan Pager Kecamatan Rakumpit: Training on Processing Chicken Meatballs with Pumpkin Flour Filling for Women's Group, Pager Village, Rakumpit District - Silitonga, Lisnawaty; Yuanita, Iis; Tambunan, Ellen Christ (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The aim achieved from this activity is to improve chicken meatball products by using alternative filler raw materials such as pumpkin flour which can increase the nutritional value of chicken meatball products and empower rural women's workforce which ultimately increases the income of families and groups of women. Processing Products with additional fillers will increase the taste value of processed chicken meatball products, especially in dealing with children who find it difficult to consume vegetables as a source of vitamin C. The problem in the partner group is that there is still no technological touch and they don't know if making chicken meatballs can be made. Filled with pumpkin flour and how to process this product to make it delicious like meatballs filled with tapioca flour also didn't know how to use good packaging equipment, but the participants had great enthusiasm in the training with punctual attendance. The partner group also continued the product manufacturing activities, especially for family needs.